Oblicz.
1.3( 2t + 1) + 2(y - 3t) =
2. -3m + 3 (1 + m) =
3. 5k - 3l + 1 + ( 6l - 5k ) =
4. 2s + 10p + 5(2 + s - 2p) =
5. 2(3z + t - 5) - (8 + t + 6z) =
6. 6( 2 + e ) - (s + 2e) + s =
7. 2 ( i - 3d + c) + 3(2d - c) - 2i + c
8. 4 (2e - m) + 2 (2m - e) =

3

Odpowiedzi

Najlepsza Odpowiedź!
2009-11-18T21:22:15+01:00
1.3( 2t + 1) + 2(y - 3t) =6t+3+2y-6ty
2. -3m + 3 (1 + m) =-3m+3+3m =3
3. 5k - 3l + 1 + ( 6l - 5k ) =5k-3l+1+6l-5k=3l+1
4. 2s + 10p + 5(2 + s - 2p) =2s+10p+10+5s-10p=7s+10
5. 2(3z + t - 5) - (8 + t + 6z) =6z+2t-10-8-t-6z=t-18
6. 6( 2 + e ) - (s + 2e) + s =12+6e-s-2e+s=12+4e
7. 2 ( i - 3d + c) + 3(2d - c) - 2i + c=2i-6d+2c+6d-3c=2i-c
8. 4 (2e - m) + 2 (2m - e) = 8e-4m+4m-2e=6e
2009-11-18T21:23:29+01:00
1.3( 2t + 1) + 2(y - 3t) = 6t+3+2y-6t=3+2y
2. -3m + 3 (1 + m) =-3m+3+3m=3
3. 5k - 3l + 1 + ( 6l - 5k ) =5k-3l+1+6l-5k=3l+1
4. 2s + 10p + 5(2 + s - 2p) =2s+10p+10+5s-10p=7s+10
5. 2(3z + t - 5) - (8 + t + 6z) =6z+2t-10-8-t-6z=t-18
6. 6( 2 + e ) - (s + 2e) + s =12+6e-s-2e+s=12+4e
7. 2 ( i - 3d + c) + 3(2d - c) - 2i + c= 2i-6d+2c+6d-3c=2i-c
8. 4 (2e - m) + 2 (2m - e) = 8e-4m+4m-2e=6e
2009-11-18T21:24:39+01:00
1.3( 2t + 1) + 2(y - 3t) = 6t+3+2y-6t=5y
2. -3m + 3 (1 + m) =-3m+3+3m=3
3. 5k - 3l + 1 + ( 6l - 5k ) =5k-3l+1+6l-5k=3l+1
4. 2s + 10p + 5(2 + s - 2p) =2s+10p+10+5s-10p=7s+10
5. 2(3z + t - 5) - (8 + t + 6z) =6z+2t-10-8-t-6z=t-18
6. 6( 2 + e ) - (s + 2e) + s =12+6e-s-2e=12+4e
7. 2 ( i - 3d + c) + 3(2d - c) - 2i + c=2i-6d+2c+6d-3c=2i-c
8. 4 (2e - m) + 2 (2m - e) = 8e-4m+4m-2e=6e

:)